2015
DOI: 10.1089/bari.2014.0032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Drain Site on Abdominal Pain after Laparoscopic Gastric Bypass Surgery for Morbid Obesity: A Randomized Controlled Trial

Abstract: Background: Most morbidly obese patients complain of abdominal pain after laparoscopic gastric bypass (LGBP) surgery. In this study, the relationship between the prevalence and severity of pain and the drain site was assessed. Methods: Fifty morbidly obese patients undergoing LGBP surgery were selected, and a drain was randomly inserted postoperatively to the left 5 mm port in 25 cases and to the right in the other 25. All patients filled out a questionnaire, including a visual analog scale for the quality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In addition to the other sequels of its removal which may occur includes bile leakage, biliary peritonitis and reoperation. 22,23 In our study, the T-tube drain was used in 36 (60%) patients who were treated by LCBDE, CBD closure was performed primarily in 20 (33.3%) patients. Patients were treated by the OCBDE T-tube was used in 35 (58.3%) and primary closure in 20 (36.3%).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition to the other sequels of its removal which may occur includes bile leakage, biliary peritonitis and reoperation. 22,23 In our study, the T-tube drain was used in 36 (60%) patients who were treated by LCBDE, CBD closure was performed primarily in 20 (33.3%) patients. Patients were treated by the OCBDE T-tube was used in 35 (58.3%) and primary closure in 20 (36.3%).…”
Section: Discussionmentioning
confidence: 87%
“…The T-tube is usually used to decompress the bile duct, provide post-operative access to ductal imaging and provide routing for removal of missed CBD stones. 9,23 On the other hand, a lot of complications related to its insertion, such as bacteremia, dislodgment, obstruction, bile infection, and wound infection. In addition to the other sequels of its removal which may occur includes bile leakage, biliary peritonitis and reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown in a study conducted with R-Y Gastric Bypass patients that interventions performed on the right side of the abdomen are more comfortable than on the left side. 14 Similarly, in a study that was conducted on laparoscopic cholecystectomy patients, it was shown that differences were found in terms of pain between the trocar sites from which the piece was removed. 15 This prompted us to think that there may be incision sites where we can apply the optimal treatment.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of subhepatic drainage on postoperative pain in patients who underwent laparoscopic cholecystectomy has been investigated by previous studies [ 13 ]. In the majority of previous studies, subhepatic drainage had no effect on postoperative pain after laparoscopic cholecystectomy [ 15 , 16 , 18 , 19 ], which is inconsistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, the use of routine administration of abdominal drainage after laparoscopic cholecystectomy has been limited to patients with intra-operative complications, including incomplete homeostasis and bile leakage [ [7] , [8] , [9] , [10] ]. While in some other studies, drainage has been reported as a postoperative pain relief agent [ [11] , [12] , [13] ]. The current evidence is discrepant regarding the efficacy of abdominal drainage for relieving postoperative pain after laparoscopic cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%